2016
DOI: 10.9708/jksci.2016.21.5.099
|View full text |Cite
|
Sign up to set email alerts
|

The role of positive affect in virtual collaboration: a transactive memory system perspective

Abstract: Creative performance has been regarded as the key to the success of an organization in recent years, and is considered essential for the survival of an organization. Organizations must find and develop creative solutions to deal with a variety of business issues. How can organizations become more creative? To develop creativity, organizations must make it easier to connect the knowledge and perspectives of its various members, who may be scattered around the world, by developing a virtual team. Drawing from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In case studies of cross-regional software development projects, Oshri found that a team could reduce misunderstandings among different members and improve software compatibility and integrity using TMS (Oshri, 2008). Chae also used cross-sectional data from 322 individuals to prove that the three dimensions of TMS were positively correlated with innovation performance (Chae et al, 2016). Due to the complexity of new product development, it is necessary to integrate and coordinate expert information from different team members and to be able to fully share it.…”
Section: Theoretical Review and Research Hypothesis Unique Informatiomentioning
confidence: 99%
“…In case studies of cross-regional software development projects, Oshri found that a team could reduce misunderstandings among different members and improve software compatibility and integrity using TMS (Oshri, 2008). Chae also used cross-sectional data from 322 individuals to prove that the three dimensions of TMS were positively correlated with innovation performance (Chae et al, 2016). Due to the complexity of new product development, it is necessary to integrate and coordinate expert information from different team members and to be able to fully share it.…”
Section: Theoretical Review and Research Hypothesis Unique Informatiomentioning
confidence: 99%